ERROR LOGS FOR BETTER ENGLISH - Begum Kut (Informascope, 2018)
The objective of this study is to investigate the common errors of L2 learners in a Turkish university setting where they have to learn L2 and pass a B1 level exam in order to be faculty students. The study aims at identifying what types of errors the learners do, what the possible determining factors at the background are and how they can overcome these. The problem areas are analysed within 17 English paragraphs of 17 Turkish students. As Corder suggested (1974) sample collection, error identification, error description, error explanation, and error evaluation are the steps followed in this study. So, first, the errors were identified; then, the errors were explained and analysed. The analysis of the writings showed that errors commonly occurred in areas of lexis, grammar, syntax and were the results of the differences between L1 and L2. As a solution, error logs were used in order to have the learners be aware of the origins of the problem areas and after the error correction, drafting was done to reflect the improvements in their writings by trying to overcome the problem of L1 interference. Keywords: error, error correction, feedback, error log, L1 interference